Estate Planning: Getting Started - Josephine Turner; Martie Gillen (EDIS)
Estate planning is a topic avoided by many people because it deals with attitudes and feelings about death, property ownership, business arrangements, marriage, and family relationships that family members may not be ready to discuss. It may also be avoided because family members disagree on how assets are to be handled. Although planning for the end of life may be uncomfortable, think of it as a gift to your family. By getting your affairs in order, you will save them a great deal of anxiety, time, and money even if you can't spare them their grief. This revised 5-page fact sheet is the first in a series on estate planning tools and techniques. Written by Josephine Turner and Martie Gillen, and published by the UF Department of Family, Youth and Community Sciences, December 2011.